MEMBANGUN SISTEM KEPROFESIAN PENYULUH PERTANIAN (DEVELOPING AN AGRICULTURE EXTENSION VOCATIONAL SYSTEM) - Husodo, Sapto (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2008)
The quality of human resource is the main key to the success of agriculture development. Experience has proven that in Indonesia agriculture extension as a part of agricultural human resources development significantly contributes to the success of many agricultural development programs. Hence, agricultural extension holds a strategic position in agricultural development. On the other hand, challenges of globalization urges extension worker to improve their skills to pace up with the changes occurring on the farmers side, who are becoming more advanced in many aspects, including perspective, knowledge, skill, as well as being more analytical. With these logics, the formulation of a vocational competency standard for agricultural extension workers is called for to strengthen their competitiveness and to develop accountability to those who benefit from agricultural extension services. The development of a competency and accreditation standardization system for government agricultural extension workers is implemented by placing extension worker either as functional staff or as professionals, while for independent and private extension agents, agricultural extension activities are merely vocational. Thus government extension workers, besides as functional staff, should also be in compliance with the accredited competence standards, proven by the possession of a vocational certificate. The competency of agricultural extension workers can be advanced towards their competency as agents of knowledge transfer to the farmer community, consisting andragogy competency, personality competency, social competency, and professional competency.